A systematic review and meta-analysis of the prognosis of language outcomes for individuals with autism spectrum disorder. (May 2018) - Brignell, Amanda; Morgan, Angela T; Woolfenden, Susan; Klopper, Felicity; May, Tamara; Sarkozy, Vanessa; Williams, Katrina
Background: Language difficulties are common in autism spectrum disorder, yet little is known about the prognosis of language in children with autism spectrum disorder. The aim of this study was to systematically review studies reporting language outcomes in individuals with autism spectrum disorder. Method: A comprehensive search strategy with a well-established sensitive prognosis filter for Medline, adapted for five other databases, was used. Included studies observed individuals diagnosed with autism spectrum disorder for ≥12 months and had ≥30 participants. Risk of bias was assessed. Results: Fifty-four studies (N = 5064) met inclusion criteria. Language outcomes were standardised assessments (n = 35), notation of presence/absence of verbal language (n = 11) or both (n = 8). Age at baseline ranged from 17 months to 26 years, duration of follow-up from 1 to 38 years. Most publications (92%) were rated medium to high risk of bias. In all but one study individuals had below-average scores at baseline and follow-up. However, in most (n = 24/25; 96%) studies reporting standard scores, individuals (aged ≤ 11 years at follow-up) progressed at a comparable rate to age-expected norms or demonstrated some 'catch up' over time. Meta-analyses found mean standard scores increased over time in three language domains (composite receptive language, composite expressive language and adaptive language). Nineteen to thirty percent of children aged five years and under gained verbal language. For children aged over five years 5–32% gained verbal language over the course of study. Age, baseline language scores, IQ and length of follow-up did not moderate between study differences in composite language or adaptive language growth or the acquisition of verbal language. Conclusion: Despite variability in study methods, findings were consistent, with the majority of studies reporting children under 11 years on average progressed at a comparable rate to age-expected norms or with some 'catchup' over time. Implications: This review provides synthesised information for families and clinicians on language development over time and on language outcomes for individuals with autism spectrum disorder. Such information can be useful for prognostic counselling and may assist planning around future resources and support needs. This review also makes recommendations regarding methodology for future studies so that prognosis can become more fine-tuned at an individual level.